2022
DOI: 10.3389/fmed.2022.911273
|View full text |Cite
|
Sign up to set email alerts
|

Higher Adherence to the Mediterranean Dietary Pattern Is Inversely Associated With Severity of COVID-19 and Related Symptoms: A Cross-Sectional Study

Abstract: Background and AimsAdherence to the Mediterranean diet (MD) has been associated with a decreased risk of developing a variety of chronic diseases that are comorbidities in COVID-19 patients. However, its association to the severity and symptoms of COVID-19 are still unknown. This study aimed to examine the association between adherence to the MD pattern and COVID-19 severity and symptoms in Iranian hospitalized patients.MethodsIn this cross-sectional study, 250 COVID-19 patients aged 18 to 65 were examined. We… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 59 publications
0
15
0
Order By: Relevance
“…Four studies reported the association between Mediterranean diet adherence and COVID-19 symptoms [20,21,24,25] with a sample size of 53,069 patients. Differing comparison of Mediterranean diet adherence score was reported across studies with one each of, continuous variable of 1-point increment, categorical variable in a cut-off determined by the authors of the study, categorical variable in tertiles, and as both categorical variable in quartiles and continuous variable of 1-SD increment, as detailed in Table 3.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Four studies reported the association between Mediterranean diet adherence and COVID-19 symptoms [20,21,24,25] with a sample size of 53,069 patients. Differing comparison of Mediterranean diet adherence score was reported across studies with one each of, continuous variable of 1-point increment, categorical variable in a cut-off determined by the authors of the study, categorical variable in tertiles, and as both categorical variable in quartiles and continuous variable of 1-SD increment, as detailed in Table 3.…”
Section: Resultsmentioning
confidence: 99%
“…The study by Zagarzadeh et al [25] found that higher Mediterranean diet adherence significantly decrease the odds for all reported COVID-19 symptoms, with OR varied between 0.06–0.34 for each symptom. Three studies reported insignificant association, with OR of each study ranging between 0.84–0.992, and p value >0.05, although the result from Yue et al [24] did reach the limit of statistical significance (OR= 0.89, 95% CI: 0.80–0.99; P-trend= 0.0549).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations